Characteristics of urban environments and novel problem-solving performance in Eurasian red squirrels - Chow, Pizza Ka Yee (Proc Biol Sci, 2021)
Urban environments can be deemed ‘harsh’ for some wildlife species, but individuals frequently show behavioural flexibility to cope with challenges and demands posed by life in the city. For example, urban animals often show better performance in solving novel problems than rural conspecifics, which helps when using novel resources under human-modified environments. However, which characteristics of urban environments fine-tune novel problem-solving performance, and their relative importance, remain unclear. Here, we examined how four urban environmental characteristics (direct human disturbance, indirect human disturbance, size of green coverage and squirrel population size) may potentially influence novel problem-solving performance of a successful ‘urban dweller’, the Eurasian red squirrel, by presenting them with a novel food-extraction problem. We found that increased direct human disturbance, indirect human disturbance and a higher squirrel population size decreased the proportion of solving success at the population level. At the individual level, an increase in squirrel population size decreased the latency to successfully solve the novel problem the first time. More importantly, increased direct human disturbance, squirrel population size and experience with the novel problem decreased problem-solving time over time. These findings highlight that some urban environmental characteristics shape two phenotypic extremes in the behaviour-flexibility spectrum: individuals either demonstrated enhanced learning or they failed to solve the novel problem.